2011
DOI: 10.1007/s11368-011-0373-0
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic pollutants affect ecosystem services of freshwater sediments: the need for a “triad plus x” approach

Abstract: Purpose Freshwater sediments and their attached microbial communities (biofilms) are essential features of rivers and lakes, providing valuable ecosystem services such as nutrient recycling or self-purification which extend beyond the aquatic environment. Anthropogenic pollutants, whether from the industrial era or as a result of our contemporary lifestyles, can negatively affect these functions with hitherto unknown consequences on ecology, the economy and human health.Thus far, the singular view of the invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 122 publications
1
38
0
2
Order By: Relevance
“…The implementation of biological processes into sediment transport equations that have traditionally been modelled as abiotic systems is expected to result in better predictions of sediment dynamics (Black et al, 2002;Righetti and Lucarelli, 2007;Gerbersdorf et al, 2011;Parsons et al, 2016). Our study confirms that extracted EPSs xanthan gum and carrageenan are not perfect analogues of natural biofilms (Perkins et al, 2004), but they are capable of introducing realistic biological cohesion into flume facilities in a fast and controlled manner for a range of commonly used conditions.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The implementation of biological processes into sediment transport equations that have traditionally been modelled as abiotic systems is expected to result in better predictions of sediment dynamics (Black et al, 2002;Righetti and Lucarelli, 2007;Gerbersdorf et al, 2011;Parsons et al, 2016). Our study confirms that extracted EPSs xanthan gum and carrageenan are not perfect analogues of natural biofilms (Perkins et al, 2004), but they are capable of introducing realistic biological cohesion into flume facilities in a fast and controlled manner for a range of commonly used conditions.…”
Section: Discussionsupporting
confidence: 71%
“…Micro-organisms are a fundamental feature of aquatic environments providing a range of ecosystem services (Gerbersdorf et al, 2011;Gerbersdorf and Wieprecht, 2015). A large variety of microbial assemblages ("biofilms") such as microphytobenthos, microbial mats and biofouling in pipes (Flemming and Wingender, 2010) are representations of microbial communities in aqueous environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia-Aragon et al 2011) have demonstrated the role of periphyton, biofilms and extracellular polymeric substances (EPS) in stabilizing channel bed sediment from erosion and resuspension, thereby limiting the remobilization of contaminated sediment. Indeed Gerbersdorf et al (2011) argue that such process understanding should be part of sediment quality assessment. Much of this work on the hydrodynamic and biogeochemical processes operating at the sediment-water interface has involved the use of experimental facilities, such as flumes and within laboratories (e.g.…”
Section: Sediment-water Interfacementioning
confidence: 99%
“…Increased hydraulic forces such as floods or dredging activities might remobilize these old burdens to become bioavailable and toxic again [16,17]. The latter has become sad reality with huge ecological and economic aftermaths e.g., during the floods in 2002 and 2014 in the East part of Germany [18][19][20]. The present investigations are reasoned by the aim to better judge on sites of high contamination risk in order to take necessary precautions and initiate countermeasures.…”
Section: Introductionmentioning
confidence: 99%